The Effect of the Special Cognitive-Behavioral Intervention on the Commitment to Exercise and Adherence to the Exercise Routine - Ahmad Derakhshanpour; Mohammad Kazem Vaez Mousavi; Hamidreza Taheri (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Although most people are aware of the advantages of physical exercise, they fail to adhere to a regular routine of exercise, which necessitates this intervention. Objectives. In this study, by controlling the moderating role of the variable of commitment to exercise, the effect of a special cognitive-behavioral intervention on the commitment and adherence to an exercise routine has been investigated in adults. Methods. The statistical population for this study comprises 635 people with over 10 years' professional experience. Of this number, 235 were selected. Then, 80 employees were randomly assigned to two groups, experimental and control, with 40 members each. The experimental group was trained in cognitive-behavioral therapy for four months over 14 sessions. To collect the data on commitment and adherence to the exercise routine, a questionnaire was used. Results. When the effect of the pretest variable on the dependent variable was adjusted, it was observed that there is a significant difference (p<0.01) between the means of the scores for commitment to exercise and adherence to exercise routine. The covariance test revealed that the difference in the adherence to exercise routine in both the experimental and control groups, after controlling the effects of commitment to exercise, was not significant (p<0.05). Conclusion. The findings show that adherence to exercise routine can be improved in people by cognitive-behavioral intervention, using the moderating role of the variable of commitment to exercise and eliminating the gap between the intention to exercise and commitment to exercise. Therefore, counselors and therapists can use the cognitive-behavioral intervention protocol to improve the commitment to exercise and adherence to exercise routine.